Post-war experience of children living in Khyber Pakhtunkhwa Orphanage care settings in Pakistan - Ali, Asif (2019)
Convention on the Rights of the Child states that children have the rights to be protected from being mistreated, physically and mentally. However, most children with post-war experience are not receiving the rehabilitation services which are entitled to them. Thus, improving the wellbeing of war-affected children and connectivity with peers and families in restoration of the damaged societies must be addressed as a significant matter of urgency. However, there is a lack of proper alternative care mechanism and policy for war affected children causing more impairment and exposing them in present child protection system of Khyber Pakhtunkhwa. The aim of this study was to develop an integrated socio-ecological framework to support war-affected children in alternative care. Bronfenbrenner's ecological model and Bowlby Attachment theory underpinned this study. Qualitative research design with phenomenology method of enquiry were employed in this study. Purposive samples were comprised of 13 war affected children, between the ages of 10 to 16, from three orphanages of Peshawar, as well as stakeholders from the government and non-government institutions. The findings of the study confirmed that the children's real-life war experiences were full of neglect, discrimination, and injustice. As expressed by the participants, the complex nature of war against terror encompassed the overall sense of insecurity and mistrust. The study also found that children from FATA and Khyber Pakhtunkhwa need greater attention in terms of safety, family conditions, community, and peer relationships. They were suffering with invisible wounds of their parents' loss and exposed to radicalization, school withdrawal, weapons use and violence. The study contributes to the knowledge on psychosocial experiences of war-affected children in Pakistan. The proposed mechanism in this study will not only improve the livelihood of children in post-conflict settings but will also reduce psychosocial stressors of war.